High-Risk HPV Oncoproteins and PD-1/PD-L1 Interplay in Human Cervical Cancer: Recent Evidence and Future Directions - Allouch, Soumaya; Malki, Ahmed; Allouch, Asma; Gupta, Ishita; Vranic, Semir; Al Moustafa, Ala-Eddin (Frontiers in Oncology, 2020)
Cervical cancer is the second most common malignancy in women worldwide, and a leading cause of cancer-related mortality in developing countries. Important etiological factors in this cancer are high-risk human papillomaviruses (HPV), as roughly 96% of cervical cancer cases are positive for these oncoviruses. On the other hand, it has been recently pointed out that E6/E7 oncoproteins of high-risk HPV can upregulate the programmed cell death-1/programmed cell death-ligand 1 (PD-1/PD-L1) axis. Likewise, several recent reports showed that checkpoint blockades targeting PD-1/PD-L1 pathways have achieved efficient clinical responses via suppressing cancer progression and improving survival in several types of human cancers including metastatic cervical cancer. In this review, we summarize recent advances in our understanding of the PD-1/PD-L1 signaling pathway and its interaction with high-risk HPV and their oncoproteins, which could have an important impact on the management of HPV-associated cancers including cervical.